Lipid Peroxidation, Prooxidant and Related Antioxidant Proteins in Various Types of Hyperlipoproteinemic Males and Control - Al-Tai, W.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thirty nine hyperlipoproteinemic (HPLic) male subject aged (48-63) year not on any of the lipid lowering drugs, attending out patient clinic at Baghdad Teaching Hospital, were included in the present study, in addition to twenty two normolipidimic male subjects of matched age were included as control throughout this study. The first part of this study was devoted to the classification of the HPLic subjects according to the serum lipid and lipoprotein profile following defined criteria. The lipid parameter including total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL) were investigated in serum of HPLic subjects included in the study. The classification was performed according to Frederickson's type, as twenty one hypercholesterlemic (type IIa), and eighteen hypertriglycerdimia (type IV) HPLic subjects. In the second part of the study, lipid peroxidation marker measured as malondialdehyde (MDA), free iron, ferritin, transrerrin (Tf) and ceruloplasmin (Cp) levels were measured in the serum of all subjects included in the study. The results indicated that significant increase was observed in the serum levels of Tc, Tg and LDL in type IIa and Type IV HPLic compared to control, and a significant decrease in HDL level in serum of both HPLic group compared to control, while no significant difference in serum HDL levels between type IIa and type IV HPLic was found. The mean MDA, free iron and ferritin levels in serum were found to be significantly higher in both types IIa and IV HPLic compared to control, also ferritin level in serum of type IV showed a significant increase over that of type IIa (257.3Â±22.7 vs. 223Â±19.2 mg/ml; p